2007 IEEE Congress on Evolutionary Computation 2007
DOI: 10.1109/cec.2007.4424630
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Genetic Algorithms for User Interface Design

Abstract: Abstract-We attack the problem of user fatigue in using an interactive genetic algorithm to evolve user interfaces in the XUL interface definition language. The interactive genetic algorithm combines computable user interface design metrics with subjective user input to guide evolution. Individuals in our population represent interface specifications and we compute an individual's fitness from a weighted combination of user input and user-interface-design guidelines. Results from our preliminary study involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…The problem of automated graphical user interface generation using GAs was discussed in [24][25][26].…”
Section: Implementation and Resultsmentioning
confidence: 99%
“…The problem of automated graphical user interface generation using GAs was discussed in [24][25][26].…”
Section: Implementation and Resultsmentioning
confidence: 99%
“…However, it is difficult to make user models,because the preferences of users are relative to the emotion, the intuition, and the domain knowledge about what they are evaluated [4].With the help of IEC, a user's psychological space is mapped to a EA's parameter space. During the past decades, swarm intelligence algorithms including GA(Genetic Algorithm),PSO(Particle Swarm Optimization) and DE(Differential Evolution)were introduced into IEC [4,7,8].…”
Section: Interactive Evolutionary Computingmentioning
confidence: 99%
“…However, it is difficult to make user models,because the preferences of users are relative to the emotion, the intuition, and the domain knowledge about what they are evaluated [4].With the help of IEC, a user's psychological space is mapped to a EA's parameter space. During the past decades, swarm intelligence algorithms including GA(Genetic Algorithm),PSO(Particle Swarm Optimization) and DE(Differential Evolution)were introduced into IEC [4,7,8]. In our proposed method, we implemented the interactive evolution computation framework based on GA. A user assigns fitness to an individual in the following three ways:1)assigning a number on a subjective grading scale;2)ranking the individual;3)choosing the best individual from a displayed subset.The first way to get fitness was chosen in our proposed IGA.In this way, the best and the worst solution will be easy to get in every iteration.However, because of the continuous work, the user usually falls into a state of fatigue after evaluation of 20-30 generations [2].…”
Section: Interactive Evolutionary Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that these operations reduce the number of generations. Another method is proposed by Quiroz et al for user interface design [23], in which the user just selects the best and worst designs in each generation. Then, the other designs are scored based on their similarity to these chromosomes.…”
Section: Review Of Literature On Reducing User Fatigue In Interactivementioning
confidence: 99%